Prevalencia de ansiedad y depresión en pacientes con dispacidades físicas de 18 años en adelante, pertenecientes a la Asociación de Gestión de Protección Especial para la Niñez y Adolescencia AGPENA. Durante el periodo noviembre 2014-mayo 2015 - Chamba Yangua, Roberth Vinicio (2015)
Disability results from the interaction between persons with impairments and attitudinal and environmental barriers that hinders their full and effective participation in society on an equal basis with others; it makes them risk patients, vulnerable to developing anxiety or depression. The research carried out in the Association of Management and Special Protection for Children and Adolescents (AGPENA) from the city of Loja, focuses on analyzing the prevalence for anxiety and depression; determine types and comorbidity in patients with physical disabilities age 18 and older; develop a psychotherapeutic proposal to restore emotional balance and symptomatic relief. The study was quality-quantitative type, longitudinal, descriptive and explanatory; has been used observation, medical history, Inventory of Situations and Responses of Anxiety (ISRA) and the Beck Depression Inventory. It took as model 30 patients with physical disabilities age 18 and older; they fulfill the inclusion criteria. It was predominated moderate anxiety (23%) and moderate depression (40%); it provides of types of anxiety like moderate anxiety (53%) severe anxiety (37%), extreme anxiety (7%) and the lowest anxiety (3%). According to the types of depression, it was detected moderate depression (40%), the average depression (23%), mild depression (20%), major depression (17%) and finally the absence of depression (0%). The comorbidity of anxiety in people with physical disabilities was moderate rate (20%) and extreme type (13%) in paraplegic patients, quadriplegics, spinal cord injury, Parkinson’s disease and cerebral palsy; it was more common in men of moderate type (40%). The comorbidity of depression was moderate rate (23%) within the group of paraplegic people, being more common in men (36.7%). With these emotional disorders in the patients, also it proposed an integrative cognitive psychotherapy plan, the involvement of patients will provide psychological coping strategies to reduce anxiety levels or depression levels, improving not only quality of life, but also by maintain control direct or indirect including the positive family environment. KEYWORDS: Disability, anxiety, depression, comorbidity, psychotherapeutic plan.